Application of Ancient Principles of Architecture in Modern Practice - DG, Marshal; A, Prakash; C, Venkatasubramanian; D, Muthu; Vignesh M, Madhan (International Journal of Engineering and Technology, 2018)
Before the advent of reinforced cement concrete and steel structures in the 20th century, structures like Arches, domes and vaults were being widely used worldwide. Arches were mainly used in span openings replacing beams. This was done based on the erstwhile cultural aesthetics and technical development in the prevailing construction methodologies. Nowadays, about 35 to 40 percentage of the total construction cost is being consumed by steel and concrete and therefore constructing a building without steel and concrete contributes to reduction in cost. Vaults and arches do not require concrete and steel but use only bricks and hence environment friendly. This paper deals with the design and construction procedure for structural members including the vault and buttress wall. It also highlights the reduction in cost when adopting vault method over conventional methods, in a residential building. The Vault prototype has been made with the studied design and concepts. The idea is to introduce this technique as a cost reduction approach and to preserve this ancient construction technique. Also, this method will be economical for construction of low cost houses up to two storeys.